A Five Year financial plan for Midtown Printing Company Incorporated - Jonathan Mico, John Nicolas Llamas, Angela Nichole Macandog, Klensch Kenrick Lagman, Karla Krisha Gonzales, Lawrence Garcia, Bernadette Javier, Reamel Keemzee Martinez and Jaycellyn Moreno. 4 0 16; 5
EXECUTIVE SUMMARY: Midtown Printing Company Incorporated is founded in 1967. Today, it is considered as one of the well-established printing companies in the country. The entity is engaged in producing yearbooks and other multimedia and graphic services, as well as printing and designing of magazines, business cards, brochures, printers, labels, invitations, corporate identity and other collateral materials suitable for corporate needs. Presently, the entity has profitability problems due to cost of sales. High cost of sales is caused by large amount of inventory and expensive raw materials being imported by the entity. This financial plan aims to provide a recommendation and action plan which the entity can use to resolve their problems in profitability for the succeeding years. After a comprehensive analysis and careful evaluation, the analyst came up with recommending the entity to reengineer its business operations. Reengineering its business operations will help the company to reduce its cost of sales to improve its profitability position. Upon doing this alternative course of action, Midtown Printing Company will now be able to achieve their financial objectives.
Financial Plan :(BSBA Major in Finance and Treasury Management)- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2